2017
DOI: 10.1002/slct.201701590
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Microstructure and Dc Conductivity of V2O5‐Nd2O3 Glass Nanocomposites

Abstract: The present work points to highlight the structural, optical and electrical properties of some semiconducting V2O5‐Nd2O3 glass nanocomposites. Structural properties such as identification of nano phases in the glassy matrix and crystallite sizes have been evaluated using X‐ray diffraction (XRD) and transmission electron microscopy (TEM). Fourier transform infrared spectroscopy (FT‐IR) and Raman spectroscopy have been used to find out nature of bonding in the as‐synthesized glass nanocomposites. Optical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…We have observed that DC activation energy (E σ ), and activation energy (E H ) for hopping frequency (ω H ) increases with increasing Fe content in glass system based on xFe ⋅ (1‐x) (0.3 V 2 O 5 ⋅ 0.2MoO 3 ⋅ 0.4CdO ⋅ 0.1ZnO) [x=0.0, 0.05, 0.10] compare with other glassy systems [12,23–24,53–54,56] (Table 1).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…We have observed that DC activation energy (E σ ), and activation energy (E H ) for hopping frequency (ω H ) increases with increasing Fe content in glass system based on xFe ⋅ (1‐x) (0.3 V 2 O 5 ⋅ 0.2MoO 3 ⋅ 0.4CdO ⋅ 0.1ZnO) [x=0.0, 0.05, 0.10] compare with other glassy systems [12,23–24,53–54,56] (Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…In the current work, the investigation of the DC electrical conductivity of amorphous semiconductors may take into account the density of defect states in the mobility gap [52–54] . Figure 6 depicts the temperature‐dependent DC electrical conductivity of the current system, demonstrating its thermally activated nature [12,23–24,53–54,56] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations